Report of the Rarities Committee of the Slovak Ornithological Society/ BirdLife Slovakia in 2023 - Marian Mojžiš; Stanislav Harvančík; Rudolf Jureček; Dušan Karaska; Dušan Kerestúr; Miloslav Mišík; Vladimír Šrank (Tichodroma)
n 2022, the Rarities Committee of the Slovak Ornithological Society/BirdLife Slovakia reviewed 52 records, of which 44 were accepted in category A, one in category C, two in category D, and two in category E. Additionally, three breeding records were accepted. Two records/one ind. of Brant Goose (Branta bernicla), one record/one ind. of Pink-footed Goose (Anser brachyrhynchus), seven records/at least five ind. of Lesser White-fronted Goose (Anser erythropus), two records/one ind. of Tundra Swan (Cygnus columbianus), one record/one ind. of Ring-necked Duck (Aythya collaris), one record/one ind. of Baillon´s Crake (Zapornia pusilla), one record/one ind. of Greater Flamingo (Phoenicopterus roseus), one record/one ind. of Terek Sandpiper (Xenus cinereus), one record/one ind. of Black-winged Pratincole (Glareola nordmanni), three records/one ind. of Pallas’s Gull (Ichthyaetus ichthyaetus), one record/one ind. of Great Black-backed Gull (Larus marinus), eight records/nine ind. of Pallid Harrier (Circus macrourus), one record/ nine ind. (first observation and nesting for Slovakia) of Eurasian Crag Martin (Ptyonoprogne rupestris), one record/ one ind. of Yellow-browed Warbler (Phylloscopus inornatus), one record/one ind. of Rosy Starling (Pastor roseus) and one record/one ind. (first for Slovakia) of Richard’s Pipit (Anthus richardi) were the most interesting records in 2022. The Rarities Committee accepted observations from the year 2022, but also some notable observations from the years 2013, 2019, and 2021. For example, one record/one ind. of Eurasian Stone-curlew (Burhinus oedicnemus), one record/one ind. of Pomarine Skua (Stercorarius pomarinus), and one record/one ind. (first for Slovakia) of Iberian Chiffchaff (Phylloscopus ibericus). In 2021, Western Cattle Egret (Bubulcus ibis) nested in Slovakia for the first time. The updated list of species and subspecies subject to reporting to the Rarities Committee of the Slovak Ornithological Society/BirdLife Slovakia, as well as the English version of the form template, is available on the following website: http://www.vtaky.sk/stranka/50-Faunisticka-komisia.html